Monitoring of the Main Reasons for Early Abandonment of Breastfeeding during the First Six Months of Life: A Secondary Analysis - María Jesús Valero-Chillerón; Francisco Javier Soriano-Vidal; Desirée Mena-Tudela; Águeda Cervera-Gasch; Rafael Vila-Candel; Irene Llagostera-Reverter; Laura Andreu-Pejó; Víctor Ortíz-Mallasén; Víctor Manuel González-Chordá (MDPI AG, 2024)
The rate of six-month-old infants exclusively breastfed in Spain remains below the recommended rate. This study aimed to explore in detail the evolution of feeding during the first six months of life of a group of newborns, as well as to identify the reasons reported by the mothers for feeding change. A secondary analysis of two prospective longitudinal observational studies was conducted. In both studies, women participants, during the clinical puerperium, opted for exclusive breastfeeding for their newborns. The participants were followed up during the infants' first six months. A sample size of 314 participants was obtained, of which 77.1% (n = 232) were of Spanish origin, and 51% (n = 160) were primiparous. The prevalence of exclusive breastfeeding at six months was 55.4% (n = 174). During the first four months of life, the main reason for early abandonment of breastfeeding was the perception of insufficient milk production. After the fourth month, the predominant reason was starting work. Statistically significant differences were observed between the reasons for giving up and the total weeks of exclusive breastfeeding (p < 0.001) and total weeks of breastfeeding (p = 0.002). Early weaning from breastfeeding is a multifactorial phenomenon. However, depending on the moment cessation occurs, some reasons predominate over others and, in many cases, can be prevented. These results indicate the need to continue investing efforts to promote and protect breastfeeding in Spain.